The little drummer girl [videorecording (DVD)] - Keaton, Diane; Voyagis, Yorgo; Kinski, Klaus; Hill, George Roy, 1921-2002; Le Carré, John, 1931- (Archive collection., 2009)
Screen adaptation of John Le Carre's bestseller about a pro-Palestinian actress who gets recruited to impersonate an Israeli agent and gets caught in the world of terrorists.